2020
DOI: 10.1186/s13062-020-00262-7
|View full text |Cite
|
Sign up to set email alerts
|

The archaeal-bacterial lipid divide, could a distinct lateral proton route hold the answer?

Abstract: The archaea-bacteria lipid divide is one of the big evolutionary enigmas concerning these two domains of life. In short, bacterial membranes are made of fatty-acid esters whereas archaeal ones contain isoprenoid ethers, though at present we do not have a good understanding on why they evolved differently. The lateral proton transfer mode of energy transduction in membranes posits that protons utilize the solvation layer of the membrane interface as the main route between proton pumps and ATPases, avoiding diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Notably, these two modules correspond to the pathways in which A501 and 3DAC should be distinct. The module from DHAP to G13P2 is the link to the biosynthesis of lipids, representing the major difference between archaea and bacteria 50 , 51 . The other is in the biosynthesis of NAD(P) + from the precursor nicotinate.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, these two modules correspond to the pathways in which A501 and 3DAC should be distinct. The module from DHAP to G13P2 is the link to the biosynthesis of lipids, representing the major difference between archaea and bacteria 50 , 51 . The other is in the biosynthesis of NAD(P) + from the precursor nicotinate.…”
Section: Resultsmentioning
confidence: 99%
“…For the bacterial premitochondrion, the loss of protons would not have been critical, (i) because bacteria have mechanisms to compensate pH shifts in any of the two directions in the environment, [ 74 ] (ii) the energetic loss involved would be compensated by the more efficient digestion, and (iii) a published hypothesis points to a special, more protected, proton route within the bacterial membrane. [ 75 ] In this scenario, acidification of the phagocytic microenvironment could potentially be more intense as it is driven by oxidative respiration.…”
Section: Resultsmentioning
confidence: 99%
“…The cristae formation is functional to better functioning of membrane H + capacitor for better functionality of ATP synthase [ 29 ]. The H + handling was also analysed and it was found that bacterial phospholipid esters enable better H + lateral currents when in a monolayer over water than the isoprenoid phospholipid ethers of archaea [ 30 ]. This is confirmatory of H + currents on the membrane for energy transfer.…”
Section: A Novel Perspective On Mitochondria Evolutionmentioning
confidence: 99%
“…Along this vision, theoretically, any membrane can be considered as a ‘proton-sponge’ on the basis of the available pH-buffers in the form of phospholipids, which with their phosphate residue can store and dispose of protons at the membrane–cytosol interface [ 43 , 44 ]. The crucial role of the bacterial phospholipid ester to allow the H + current which entails interesting evolutionary considerations was recently highlighted [ 30 ]. On the other hand, the existence of H + conductors [ 45 47 ] and of H + microcircuits in membranes has been highlighted [ 48 ].…”
Section: Proton Movements In the Respiring Membranementioning
confidence: 99%